2004
DOI: 10.1253/circj.68.623
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the Risk Factors for Coronary, Renal and Other Peripheral Arteriosclerosis in Heterozygous Familial Hypercholesterolemia

Abstract: therosclerotic lesions in an individual do not progress at a same rate, 1 despite the systemic atherosclerosis risk factors affecting all arteries uniformly. The severity and extent of lesions differ throughout the body 2 and although the topographic distribution of atherosclerotic lesions in rabbits fed a low-level cholesterol diet has been shown, 3 no studies of humans have been conducted to date.Familial hypercholesterolemia (FH) is characterized by accelerated atherosclerotic lesions, and because the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In other studies, the risk of this complication was 5 to 10 times greater than that in controls 36) . The prevalence of iliac artery disease (more than minimal) in FH patients in Japan was 56% 37) . Information on cerebrovascular or peripheral artery disease in Korean FH patients remains to be evaluated.…”
Section: Genetic Characteristicsmentioning
confidence: 98%
“…In other studies, the risk of this complication was 5 to 10 times greater than that in controls 36) . The prevalence of iliac artery disease (more than minimal) in FH patients in Japan was 56% 37) . Information on cerebrovascular or peripheral artery disease in Korean FH patients remains to be evaluated.…”
Section: Genetic Characteristicsmentioning
confidence: 98%
“…In the current study, FH was diagnosed by our clinical criterion 2,18,19 and confirmed by genetic method in 14 of the 15 enrolled patients. 18,19 We failed to find the LDL receptor gene mutation in 1 patient, whose baseline LDL-C concentration was almost the average for heterozygous FH, namely 262 mg/dl.…”
Section: Discussionmentioning
confidence: 68%
“…18,19 We failed to find the LDL receptor gene mutation in 1 patient, whose baseline LDL-C concentration was almost the average for heterozygous FH, namely 262 mg/dl. Because no patient with familial defective apolipoprotein B has been reported in Japan, 32 it is possible that perhaps this particular patient might be another case of autosomal dominant hypercholesterolemia, such as PCSK9 gene mutation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the peripheral arteriosclerotic diseases, the clinical significance of renal arteriosclerosis (RAS) may have been underestimated despite its causal relationship with renovascular hypertension and nephrosclerosis. Yagi et al [8] reported atherosclerotic changes in coronary arteries, abdominal aorta, and iliac and renal arteries in adult FH patients, and most cases of RAS (64%) presented with <25% stenosis. Yokoyama et al [9] also angiographically demonstrated that atheromatous lesions regressed in the aortic valve region and in the left renal artery in a patient with homozygous FH who was treated with long-term, repetitive LDL-C apheresis.…”
Section: Discussionmentioning
confidence: 99%